RANCANG BANGUN MODEL SLIM FLAT WALL (SFW) AQUARIUM SEBAGAI MEDIA KONSERVASI IKAN HIAS PROMOTIF UNTUK BANGUNAN MINIMALIS - Kaminton Tambunan; Raman G.T.H. Simanjuntak; Novie Wijaya; Andie Murtono; Dwi Dharma Arta Kusuma; Ahmad Ilham Ramadhani; Mukhlis Mukhlis; Muhamad Amril Idrus; Febi Luthfiani (Universitas Mataram, 2026)
This study developed a Slim Fit Wall (SFW) Aquarium as a medium for ornamental fish conservation and a decorative element for minimalist buildings. The aquariums were designed to be slim with dimensions of 80 × 10 × 40 cm and 100 × 10 × 60 cm, using glass materials and lightweight steel brackets. This design offers a space-saving solution without sacrificing visual and functional aspects. Testing involved strength simulations using Autodesk Inventor software, showing Von Mises stresses below the material's safe limit, ensuring structural strength. Visual and functional tests were conducted with respondents from the KP Kupang Polytechnic. The results showed an average visual satisfaction level of 83.9%, with advantages in space efficiency and visual comfort. Functionality was tested for one month, demonstrating stable performance without component damage. The study's conclusion confirms that the SFW Aquarium is suitable for minimalist buildings, fulfilling aesthetic needs, and supporting conservation awareness. Further research is recommended to explore variations in size and design.